Кон Marcel Conche, Quelle philosophie pour demain? Për Marcel Conche, Quelle philosophie pour demain? - Sekulovski, Jordančo; Ahmeti, Xhabir (Identities: Journal for Politics, Gender and Culture, 2007)
Author(s): Jordančo Sekulovski | Јорданчо Секуловски Title (Macedonian): Кон Marcel Conche, Quelle philosophie pour demain? Title (Albanian): Për Marcel Conche, Quelle philosophie pour demain? Translated by (Macedonian to Albanian): Xhabir Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 1 (Winter 2007) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 239-243 Page Count: Citation (Macedonian): Јорданчо Секуловски, „Кон Marcel Conche, Quelle philosophie pour demain?“, Идентитети: списание за политика, род и култура, т. 6, бр. 1 (зима 2007): 239-243. Citation (Albanian): Jordančo Sekulovski, „Për Marcel Conche, Quelle philosophie pour demain?“, përkthim nga Maqedonishtja Xhabir Ahmeti, Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 1 (Winter 2007): 239-243.